The Efficacy of 480 ml Oral Sodium Sulfate for Improving Insufficient Bowel Preparation of Colonoscopy with High-Concentrated Polyethylene Glycol - Naohisa Yoshida; Yoshikazu Inagaki; Daisuke Hasegawa; Reo Kobayashi; Yuri Tomita; Hikaru Hashimoto; Ryohei Hirose; Osamu Dohi; Ken Inoue; Yasutaka Morimoto; Yutaka Inada; Takaaki Murakami; et al. (Gastroenterology Research and Practice)
Objectives. Oral sulfate solution (OSS) is used for bowel preparation (BP) during colonoscopy. The way of taking this agent can be used a same-day regimen (only on the day of colonoscopy) and split regimen (the day before and on the day of colonoscopy) for receiving it. In this study, we analyzed the efficacy of a same-day regimen of 480 ml OSS for insufficient bowel preparation (BP) with high-concentrated polyethylene glycol (H-PEG). Materials and Methods. This multicenter retrospective study was conducted from December 2021 to December 2022 at three related institutions on patients aged≥20 years with a fair or poor Aronchick score of BP with 1 l H-PEG in previous colonoscopy. All patients received a low-residual diet and 10 ml of 0.75% picosulfate sodium a day before the colonoscopy and 480 ml of OSS and ≥1 l of water 3 hours before the colonoscopy. We analyzed the rate of improvement with OSS compared to H-PEG and other efficacies, and adverse events (AE). Results. We evaluated 125 cases (77 males) with an average age of 72.1±8.8 years. The completion rate of 480 ml of OSS was 97.6% (122/125). The improvement rate of BP showing good or excellent score with OSS was 70.4% (88/125). Compared OSS with previous H-PEG, the insertion time (min) was 7.0±4.8 vs. 8.1±6.0 (p=0.01), and the adenoma detection rates were 67.2% vs. 63.2% (p=0.05). The cleansing time (min) was 131±46 vs. 165±53 (p<0.01). The rate of AE with OSS was 10.4% (13/125). There were no significant differences about AE in age and gender. The tolerance of OSS compared with H-PEG (good/similar/bad) was 72.0%/24.8%/3.2% (amounts), 26.4%/39.2%/34.4% (taste), and 76.8%/10.4%/12.8% (overall preference), respectively. Conclusions. The same-day regimen of 480 ml OSS effectively improved the insufficient BP of 1 l H-PEG.